Innovation PAUD curriculum for Increase Quality of Early Childhood Education - Hawa Saputri (Pt. Anagata Sembagi Education, 2024)
Childhood Education (PAUD) is very important in develop base cognitive , social , emotional , and physical child . Innovation PAUD curriculum , incl method teaching interactive and use technology , yes increase quality education with make learning more interesting and appropriate with need child . Study This use method qualitative , incl interviews , observations , and discussions group , for evaluate impact innovation curriculum . Findings show that method interactive and technological support engagement and development child in a way positive . Parental involvement and aspects​ inclusivity also contributes to success curriculum . Challenges faced​ including need training for teachers and providers source Power . Curriculum innovative potential increase quality PAUD education with create environment relevant and inclusive learning .​